Stress concentration factor of a variable circular cross section beam under flexion (Revista Cientifica Ingenio Magno, 2023)
Fatigue testing in rotating beam fatigue systems requires the usage of specimens with standardized geometry, which exhibits a changing cross section to guarantee that the failure occurs within the gauge length. The proper calculation of the stress within the gauge length requires that a stress concentration factor is calculated, which has not been previously reported by the specialized literature. Therefore, in this work both the Finite Element Method and the Beam Theory was used aimed at calculating the calculation of stress concentration factor of a specimen with complex cross section change. For that, half specimen was modeled in a finite elements software as a cantilever beam and the stress in the supported end was determined. Analytically, stress of the testing machine under the consideration of a four-point bending beam was calculated. Results of both calculations were compared in order to establish the stress concentration factor. It was determined that, without considering the stress concentration factor, stress of the specimen calculated with analytical beam theory is 24% smaller than that obtained with the finite element software.
Keywords: rotating beam fatigue testing machine, dog-bone shaped specimen, finite element method, stress concentration factor, variable cross section beam